Higher Education Institutions in Bosnia and Herzegovina use Social Network Sites? (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The paper presents the research of the current state of the presence and activities of higher education institutions in Bosnia and Herzegovina (BiH) on social network sites (SNS). Although higher education institutions in BiH have recognized the necessity of using social networks for communications with their stakeholders, especially students, they still struggle with the content posted on SNS and its frequency. The authors use content analysis to examine SNS posts from BiH higher education institutions and engagement from their constituents on these posts. Results show that there are significant differences in engagement received on posts across institution type and according to content and type of posts. The aim of the paper is to analyze if HEIs in BiH use SNS and to what degree, as well as if there is any difference between public and private institutions related to the usage of SNS.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.